The use of Ag-NOR stain to determine the proliferative activity of cervical intraepithelial neoplasia - Faisal, Ghasak Ghazi; Hussein, Alla'a Ghani (2012)
Objective : To determine the proliferative activity of cervical intraepithelial lesions to assist in the diagnosis and treatment of these lesions through the use of silver stained nucleolar organizer region (Ag +– NOR). Nucleolar organizer regions (NOR) are loops of ribosomal DNA (rDNA) occurring in the nuclei of cells.Cell proliferation under normal physiological conditions is accompanied by increased ribosome biogenesis .The amount of Ag-NOR proteins present during interphase is routinely used to evaluate nucleolar activity and cell proliferation. Thus quantification of Ag-NOR proteins is applied to characterize human cancer cell proliferation ; high levels of Ag-NOR proteins indicate a high rate of proliferation .